The effect of surgical treatment on voice quality in Reinke's edema: an evaluation with vocal performance questionnaire and acoustic voice analysis - Taşar, Soner; Kezban Gürbüz, Melek; Kaya, Ercan; Özüdoğru, Erkan; Güney, Fatma; Çaklı, Hamdi; İncesulu, Armağan (ENT Updates, 2013)
Objective: The aim of this study was to investigate the effect of surgical treatment of Reinke's edema on voice quality. The changes in voice quality caused by surgical treatment were evaluated by using voice performance questionnaire and acoustic voice analysis before and after surgery. Methods: Vocal Performance Questionnaire and acoustic voice analyses with the help of Dr. Speech (Drs Tiger Inc., Seattle, WA, USA) software were performed preoperatively and at one month postoperatively in 21 patients with Reinke's edema who had received surgical therapy. Results: Reinke's edema was bilateral in all patients. According to the results of vocal performance questionnaires and acoustic voice analyses, the voice quality of patients improved significantly after surgery. At the end of the six month follow-up, the recurrence was detected only in one (4.7%) patient. Conclusion: In patients with Reinke's edema, the functional properties of vocal folds and the voice quality of patients can be successfully improved by surgical treatment.